Development of a wellness program and supporting materials for Rise up scholars - Wilcox, Harold (My University, 2024)
Sedentary behavior has become a significant public health concern in America, contributing to the rise of obesity and a host of negative health outcomes, including cardiovascular disease, diabetes, and mental health issues. As more adults adopt sedentary lifestyles due to the nature of their work, these behaviors not only affect their health but also place a growing burden on the healthcare system. Addressing these behaviors early, before they solidify into adulthood, is critical to preventing long-term health complications. One potential intervention point is during the college years, where students are transitioning into adulthood and are particularly open to learning new habits that can shape their future behaviors. College students are often vulnerable to adopting sedentary lifestyles due to academic pressures, lack of resources, and limited health education. The college setting provides a unique opportunity to introduce positive health behaviors that can counteract the sedentary tendencies many students may face as they transition into the workforce. This is particularly important for business students, who are likely to enter office jobs that often involve long hours of sitting and little physical activity. By instilling healthier habits during their college years, students can be better prepared to manage their well-being in their future careers. My Applied Practical Experience with the Rise Up Wellness program at Kansas State University aimed to address this issue by targeting a cohort of College of Business students, a population that is especially susceptible to sedentary behaviors. Through the program, I designed and implemented a series of wellness activities and educational sessions that emphasized the importance of physical and mental wellness, with the goal of preparing students for healthier, more productive lives both during and after their academic careers. The program sought to reframe health behaviors as professional skills that can enhance quality of life and performance in the workplace. The goals, activities, and products developed during my APE were guided by my educational background in kinesiology and public health. My educational coursework, literary review, and semester projects such as the ones completed in KIN 610 and KIN 805, provided the foundation for understanding the complex relationship between sedentary behavior, health outcomes, and the workplace, while my practical experiences allowed me to apply this knowledge in a real-world setting. The creation of program materials, such as the syllabus, evaluation tools, and partnership strategies, allowed me to refine my skills in program planning, evaluation, and communication. These experiences not only contributed to the creation of the Rise Up Wellness program but also enhanced my development as a student and public health professional, preparing me for future roles in promoting wellness in diverse settings.
Keywords: Social Cognitive Theory; Self Determination Theory; Exercise; Self-efficacy; Program design and evaluation